2009
DOI: 10.1088/0741-3335/51/12/125001
|View full text |Cite
|
Sign up to set email alerts
|

Beam-ion confinement for different injection geometries

Abstract: The DIII-D tokamak is equipped with neutral beam sources that inject in four different directions; in addition, the plasma can be moved up or down to compare off-axis with on-axis injection. Fast-ion data for eight different conditions have been obtained: co/counter, near-tangential/near-perpendicular and on-axis/offaxis. Neutron measurements during short beam pulses assess prompt and delayed losses under low-power conditions. As expected, co-injection has fewer losses than counter, tangential fewer than perpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 55 publications
5
51
0
Order By: Relevance
“…The broadened beam ion profile is consistent with D EI ¼ 0:5 m 2 =s, implying a considerable transport mechanism. Off-axis NBCD at DIII-D produced an example 44,45 of a similar process, with the transport enhancement increasing with P NB (since the beam energies are fixed at E b % 80 keV, this corresponds to a decreasing E b =T e ). A value of D EI ðrÞ ¼ 0:5v i ðrÞ, where v i is the power-balance computed ion thermal diffusivity, did not reduce the energetic ion density enough to agree with the experimental profile, and further increasing D EI produced greater discrepancy between the measured and simulated profile shapes.…”
Section: A Experiments and Modelingmentioning
confidence: 91%
“…The broadened beam ion profile is consistent with D EI ¼ 0:5 m 2 =s, implying a considerable transport mechanism. Off-axis NBCD at DIII-D produced an example 44,45 of a similar process, with the transport enhancement increasing with P NB (since the beam energies are fixed at E b % 80 keV, this corresponds to a decreasing E b =T e ). A value of D EI ðrÞ ¼ 0:5v i ðrÞ, where v i is the power-balance computed ion thermal diffusivity, did not reduce the energetic ion density enough to agree with the experimental profile, and further increasing D EI produced greater discrepancy between the measured and simulated profile shapes.…”
Section: A Experiments and Modelingmentioning
confidence: 91%
“…1 of Ref. 9. The vertical extent of the neutral beams is most recently calculated and experimentally verified in Ref.…”
Section: ͑1͒mentioning
confidence: 81%
“…Before examining those calculations directly, it is useful to compare measurements and modeling of the neutron evolution before and after a step change in the neutral beam power. Previous experiments have studied the behavior of "dilute" populations of fast ions [32,49,50,74], including studies in NSTX L--mode plasmas [74]. The latter study showed that the prompt loss and slowing down of fast ions in those plasmas were consistent with classical behavior.…”
Section: : Comparison Of the Measured And Simulated Neutron Dynamicsmentioning
confidence: 94%
“…Alfven modes have also been shown to modify the current profile [63,64]. Recently, evidence from DIII--D [49,50] and ASDEX--Upgrade [60] has indicated that the electrostatic turbulence responsible for thermal plasma transport may also lead to radial diffusion of the injected fast ions.…”
Section: : Introductionmentioning
confidence: 99%